SRA Open Court reading. (SRA/McGraw-Hill, 2002)
Teaches children through a systematic and explicit scaffolding of program assessment skills that build upon each other. By taking into account the individual needs of students and providing them with practice and reading materials, this title helps students become confident and successful readers